Risk factors for non-communicable diseases among overweight and obese women of Somali background in Oslo, Norway - Linn Bohler; Haakon E. Meyer; Maria J. Leirbakk; Mia Charlott Wedegren; Hege G. Rangsvag; Marte K. Kjollesdal; Mark L. Wieland; Ahmed A. Madar (Elsevier, 2023)
Background: Non-communicable diseases (NCDs) are the most common causes of morbidity and mortality globally. Somalis are a relatively new immigrant group in Norway and knowledge about their health status and risk factors for NCDs is limited. This study aimed to determine the prevalence of selected risk factors for NCDs among overweight and obese women of Somali background in Oslo, Norway. Methods: Baseline data of an exercise intervention study among women of Somali background (n = 168, recruited between September 2020 and September 2022). Body mass index (BMI) (kg/m2), waist-hip-ratio (WHR), blood pressure, glycated hemoglobin (HbA1c), non-fasting glucose, and blood lipids were measured. Results: Mean (SD) age was 46.8 years (10.4) and BMI was 33.9 kg/m2 (5.1). Mean total cholesterol (TC), low-density lipoprotein (LDL), HbA1c, non-fasting glucose, and blood pressure were within the normal range on average. Per one unit increase in BMI systolic blood pressure (SBP) increased by 0.89 mm/Hg (95%CI: 0.35−1.44, P = 0.002) and diastolic blood pressure (DBP) increased by 0.46 mm/Hg (95%CI: 0.17−0.75 P = 0.002). No relation between BMI and HbA1c, blood lipids, age, education level, number of children in the household, or length of residence in Norway was found. Conclusion: Despite the high BMI, most of the selected risk factors for NCDs had mean values within the normal range. The participants had a low prevalence of diabetes type 2 and hyperlipidemia, although there was a moderate association between BMI and blood pressure. This indicates that it is possible to be obese and be of relatively good health in this population. Trial registration: The study was registered at clinicaltrials.gov NCT04578067.